WHAT ARE THE PHYSIOLOGICAL RESPONSES OF STEP - AEROBIC EXERCISES IN SEDANTER WOMEN? - Turgut, Mine; Bozkus, Taner (Int Journal Lifescience & Pharma Research, 2021)
This study was aimed to investigate the effect of a 12-week step-aerobic exercise program applied to sedentary women on some physical and physiological parameters. Sixteen voluntary sedentary women with a mean age of 20.2 +/- 1.3 years were included in the study. In the study, height, body weight and BMI were measured by the researchers, and before and after the exercise program of the participants' blood samples were taken with an empty stomach in the morning by experts in an appropriate laboratory environment in the health institution. The data obtained in the research were analysed using the SPSS 22.0 package program. Nonparametric tests Wilcoxon Signed Ranks Test was used to reveal the difference between the pre-test and post-test values of the research group. According to the results obtained, it was determined that there was a significant difference between the blood lipids such as Triglyceride, HDL, LDL and total cholesterol levels before and after the step-aerobic exercise program (p <0.05). As a result of the applied step-aerobic exercise program; it was seen that there was a significant improvement in physiologically sedentary women. Step-aerobic exercises can be an exercise program that can be preferred both to lead a healthy life and to reach the desired body mass index. Besides, it was thought that it might have a protective effect from metabolic disorders that may occur.
Keywords: Step Aerobics; Exercise; Blood Fats